How have past fire disturbances contributed to the current carbon balance of boreal ecosystems? - C. Yue (Biogeosciences, 2016)
Boreal fires have immediate effects on regional carbon budgets by emitting CO2 into the atmosphere at the time of burning, but they also have legacy effects by initiating a long-term carbon sink during post-fire vegetation recovery. Quantifying these different effects on the current-day pan-boreal (44–84° N) carbon balance and quantifying relative contributions of legacy sinks by past fires is important for understanding and predicting the carbon dynamics in this region. Here we used the global dynamic vegetation model ORCHIDEE–SPITFIRE (Organising Carbon and Hydrology In Dynamic Ecosystems – SPread and InTensity of FIRE) to attribute the contributions by fires in different decades between 1850 and 2009 to the carbon balance of 2000–2009, taking into account the atmospheric CO2 change and climate change since 1850. The fire module of ORCHIDEE–SPITFIRE was turned off for each decade in turn and was also turned off before and after the decade in question in order to model the legacy carbon trajectory by fires in each past decade. We found that, unsurprisingly, fires that occurred in 2000–2009 are a carbon source (−0.17 Pg C yr−1) for the carbon balance of 2000–2009, whereas fires in all decades before 2000 contribute carbon sinks with a collective contribution of 0.23 Pg C yr−1. This leaves a net fire sink effect of 0.06 Pg C yr−1, or 6.3 % of the simulated regional carbon sink (0.95 Pg C yr−1). Further, fires with an age of 10–40 years (i.e., those that occurred during 1960–1999) contribute more than half of the total sink effect of fires. The small net sink effect of fires indicates that current-day fire emissions are roughly balanced out by legacy sinks. The future role of fires in the regional carbon balance remains uncertain and will depend on whether changes in fires and associated carbon emissions will exceed the enhanced sink effects of previous fires, both being strongly affected by global change.